The Mediator Effect of Leader- Member Exchange on the Relationship Between Organizational Cynicism and Organizational Climate - Kubilay Özyer; Ahmet Mumcu (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
The purpose of this study is to investigate the mediating role of leader-member exchange on the effects of organizational climate sub-dimensions on organizational cynicism dimensions. For this purpose, the research was carried out on 319 bank personnel. Structural equation modelling is used to test research hypotheses. According to research findings, it was found that all organizational climate dimensions had positive effect on leader-member exchange whereas leader-member exchange affected cognitive and affective cynicism negatively. When we analyzed the significant and negative effects of organizational climate sub-dimensions' on cognitive and affective cynicism, it was found that leader-member exchanges has partial and full mediatory roles. According to the results obtained from the research model, the positive climate (work atmosphere) in the organization allows the employee to interact with the leader more easily and positively. Through the leader-member exchange, the cognitive and affective cynicism perceived by the employee declines indirectly.
Keywords: 650; Leader-Member Exchange Theory; Organizational Climate; Organizational Cynicism